Intranasal administration of a panreactive influenza antibody reveals Fc-independent mode of protection - Anna L. Beukenhorst; Keira L. Rice; Jacopo Frallicciardi; Martin H. Koldijk; Carolyn M. Boudreau; Justin Crawford; Lisette A. H. M. Cornelissen; Kelly A. S. da Costa; Babette A. de Jong; Stephanie Fischinger; Boris Julg; Jaco M. Klap; et al. (Scientific Reports)
Abstract Monoclonal antibodies have two core mechanisms of protection: an antibody’s antigen-binding fragment (Fab) can bind and neutralize viral pathogens and its fragment crystallizable domain (Fc) catalyzes effector functions. We investigated the relative contribution of Fab- versus Fc-mediated mechanisms of protection through passive administration of distinct forms of the pan-reactive anti-influenza antibody CR9114. We demonstrated that the contribution of Fc-independent (Fab-dependent) versus Fc-dependent mechanisms of protection is defined by the route of administration. We used CR9114 variants (wild-type, two Fc-silenced variants, or the bivalent antigen-binding fragment F(ab′)2), administered either intravenously or intranasally. We found that intravenously-administered CR9114 requires the Fc domain to provide potent, pre-exposure protection against influenza A and B viral challenge. In contrast, when CR9114 was administered locally to the nasal mucosa, the main mode of protection was provided by F(ab′)2, and was largely Fc-independent. Importantly, this mode of protection following intranasal administration also applied to non-neutralized influenza B strains. Moreover, intranasal administration resulted in an increase in potency against influenza A/H1N1, A/H5N1, A/H3N2, B/Yam and B/Vic compared to intravenous administration up to 50-fold. These results shed new light on the application of monoclonal antibodies such as CR9114 to combat viral infection locally, and will help inform clinical strategies of pre-exposure prophylaxis. More fundamentally, this study uncovers distinct modes of protection for systemic versus intranasally-administered prophylactic antibodies.